2000
DOI: 10.1093/brain/123.6.1247
|View full text |Cite
|
Sign up to set email alerts
|

Dominant partial epilepsies: A clinical, electrophysiological and genetic study of 19 European families

Abstract: Nineteen families with autosomal dominant partial epilepsy were analysed clinically and electrophysiologically in detail. Seventy-one patients were studied as well as 33 non-epileptic at-risk family members. We subdivided the families into those with autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) (n = 8), familial temporal lobe epilepsy (n = 7) and autosomal dominant partial epilepsy with variable foci (n = 4). However, the application of this nosology to certain families was difficult in cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 39 publications
4
50
0
1
Order By: Relevance
“…EEGs were interpreted by two independent clinical neurophysiologists who were blind to the status of individuals. Focal epileptiform EEG abnormalities were defined as previously described 23 and non-epileptiform abnormalities as intermittent slow waves consistently located over the same area. MRI (1.5 Tesla unit) was performed in 5 of 9 affected members.…”
Section: Subjects and Methods Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…EEGs were interpreted by two independent clinical neurophysiologists who were blind to the status of individuals. Focal epileptiform EEG abnormalities were defined as previously described 23 and non-epileptiform abnormalities as intermittent slow waves consistently located over the same area. MRI (1.5 Tesla unit) was performed in 5 of 9 affected members.…”
Section: Subjects and Methods Subjectsmentioning
confidence: 99%
“…A disease allele frequency of 0.0001 and a penetrance of 70% were estimated using a method previously described. 23 Simulations, with the abovementioned parameters, gave a maximum pairwise lod score of 3.1 at ϭ 0.0 with a 5 allele marker of equal frequency. A whole genome scan, excluding chromosome X, was performed assuming equal frequencies for the alleles observed in the family.…”
Section: Linkage Analysismentioning
confidence: 96%
“…Ictal video-electroencephalographic studies revealed partial seizures originating from the frontal lobe. The onset is usually in childhood, inheritance is autosomal dominant, and the penetrance approximately 70±80% Picard et al, 2000]. ADNFLE has often been misdiagnosed as paroxysmal nocturnal dyskinesia, sleep disorders such as night terrors or nightmares, or hysteria [Scheffer et al, 1994].…”
Section: Autosomal Dominant Nocturnal Frontal Lobe Epilepsy (Adnfle)mentioning
confidence: 99%
“…Paroxysmal arousals, dystonia-like attacks, and epileptic nocturnal wanderings are also part of the phenotype [120]. Ictal video-EEG studies have revealed partial seizures originating from the frontal lobe, but also from parts of the insula and temporal lobe, suggesting a defect of a broader network [121,122]. A mutation in the gene CHRNA4, encoding the α4-subunit of a neuronal nicotinic acetylcholine receptor (nAchR), was the first ion channel mutation found in an DS Dravet syndrome; ID intellectual disability; IS infantile spasms;…”
Section: Autosomal Dominant Nocturnal Frontal Lobe Epilepsymentioning
confidence: 99%